SELECTIONS OF THE AKSHEMSEDDİN’S POETS - Muhammed Ali YILDIZ (Fırat University, 2020)
Akşemseddin is an eminent figure, who has become famous for his role in the conquest of Istanbul, which is the beginning of a new age. As the head teacher of Fatih Sultan Mehmet, Akşemseddin surely has a lasting impression on his student and the conquering of Istanbul. He almost conditioned him for the conquest of Istanbul since his early ages. He encouraged and created solutions in the event of trouble and pessimism that occurred during the conquest. Yet, Akşemseddin, beyond his role mentioned above, is a kind of ocean with his many unknown characteristics. He wrote nineteen works throughout his life. His works are Risaletü’n- Nuriyye, Def’u Metaini’s-Sûfiyye, Risale-i Zikrullah, Risale-i Şerh-i Akval-i Hacı Bayram-ı Velî, Telhisu Def’î Metain, Makâmâtü’l- Evliyâ, Mâddetü’l-Hayat, Risâletü’d-Dua, Fâ’il-i Mushaf-ı Kerim, Nasihatnâme-i Akşemseddin, Kimyâ-yı Sa’âdet Tercümesi, Risâle Fi’t-Tasavvuf, Risâle-i Fi’d-Devrâni’s-Sûfiyye ve Raksihim, Mücerrebât, Mektûbât, Vakıf-Nâme, Risâle Fî İstilâhâti’s-Sufiyye, Cevapnâme ve Tabirnâme. Most of his books are on Sufism and religion. His work “Maddetü’l-Hayat” is on medicine and pharmacy. In this work, he makes a detailed description of “microbe”. French microbiologist Pasteur is accepted to be the first man who described the “microbe”. However, Akşemseddin comprehensively described the microbe and explained how infectious diseases passes from person to person in his mentioned work about five hundred years earlier than Pasteur. In this work, I will also dwell on eighty-three poems which are found about fifty years ago by Müjgan Jumbur, the manager of Ankara National Library, and definitely known to be written by Akşemseddin. These eighty-three poems can be accepted as his twentieth work “Akşemseddin Poetry” in addition to his previously mentioned works. We aim to put some of these poems into service of science world after we latinised them in this work. I will add original manuscript images of these poems that we obtained from National Library to the end of this work. Our ultimate aim is to publish “Akşemseddin Poetry” as a book, which was discovered fifty years ago and not published yet.